The challenges of sustainability in business: how governments may ensure sustainability for offshore firms - Al-Amin, Abul Quasem; Filho, Walter Leal; Kabir, M. A. (Technological and Economic Development of Economy, 2018)
This study illustrates some of the challenges of sustainability for businesses and the probable causes of these challenges in relation to Malaysian offshore firms. This study highlights the possible links between business sustainability in the existing types of offshore outsourcing business environments and their failure to transform themselves to adopt best practices. The results of the statistical techniques used to quantify long-term business sustainability indicate that the age of firms has a weak relationship with sustainability and environmental practices (–0.075) and offshore outsourcing issues (0.074). Our study simulations suggest that government support amounting to 5% of export earnings would ensure offshore investment sustainability in the long term, compared to existing situations. The findings also highlight that this percentage could gradually be increased by 10%, 15% or even 20%, subject to different levels of offshore operations, outsourcing prospects, export earnings, performance and economic development. First published online 2 November 2015